1993
DOI: 10.1002/path.1711700412
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the renal arterial tree by fractal analysis

Abstract: To determine whether the renal arterial system has a fractal structure, the fractal dimension of renal angiograms from 52 necropsy cases was measured using an implementation of the box-counting method on an image analysis system. The method was validated using objects with known fractal dimensions. The method was accurate with errors of less than 1.5 per cent and reproducible with initial values within 1.2 per cent of the mean of ten sets of measurements (reliability coefficient 0.968, 95 per cent confidence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 17 publications
2
21
2
5
Order By: Relevance
“…The basic idea to build such a method stems from the complexity of living being and fractal nature of many physioanatomic structures [31] . Seve ral structures and functions of human body have got fractal properties [62,72,73] . Trabecular bone, in addition to be a good model for fractal analysis in biological structures, offers the opportunity of analyzing fra ctal lacunarity [74] .…”
Section: Bone Structurementioning
confidence: 99%
“…The basic idea to build such a method stems from the complexity of living being and fractal nature of many physioanatomic structures [31] . Seve ral structures and functions of human body have got fractal properties [62,72,73] . Trabecular bone, in addition to be a good model for fractal analysis in biological structures, offers the opportunity of analyzing fra ctal lacunarity [74] .…”
Section: Bone Structurementioning
confidence: 99%
“…28) Fractal geometric analysis has been applied in the analysis of neuronal dendritic arborizations, 29) vascular heterogeneity in the heart, 30) formation of human retinal blood vessels in the kidney, 31) the structure of the bronchial tree, 32,33) and the distribution and quantification of arterial blood vessels in the kidney. 34,35) Recently, in the field of pathology, fractal dimensions of the histological structure of colorectal polyps 17) and cell growth patterns in human malignant tumors 36) have been reported. Cross et al 17) have suggested that the fractal dimension is a better way of quantitating polyp shape and is a useful morphometric discriminant among diagnostic categories.…”
Section: Discussionmentioning
confidence: 99%
“…Whether a given network has fractal characteristics should not be taken a priori, but as a hypothesis that requires empirical validation. An abundant literature has been devoted to the fractal properties of biological features (see, for a review, Losa 15 ), among them the pattern of the vascular network 10,13,16,17 , which have been described as a combination of scale-invariant and scale-specific patterns17. What it is important to notice is that these kinds of structural analysis of vascular networks are grounded on physicomathematical concepts and tools.…”
Section: Form and Function Of Vascular Networkmentioning
confidence: 99%